Dinamiche identitarie nel contesto coloniale ne L’abbandono. Una storia eritrea di Erminia Dell’Oro - Kłosek, Wiesława (Romanica Silesiana)
The main goal of the present analysis is to show the formation of four characters’ identity in the colonial times. The analyzed novel is set in an Italian colony called Eritrea. There are four main characters: Carlo from Italy, Sellas from Eritrea, and their children Marianna and Gianfranco. They are all interpreted with reference to the three concepts related to the notion of belonging, namely, “I,” “we,” and “others.” The changes which take place in their personal and social identities are examined, as the characters form bonds with one another and with the society. They are examined as representing the following identity models: “individual identity,” “social identity,” “balanced identity” and “lack of identity.” These forms of identity, however, are never definitive because the shaping of identity is always a dynamic process, and thus every social or cultural context may require that identities be reformulated. The novel may be interpreted not only as the memoirs of the colonial times, but also as a tribute paid to the colonists, the colonised, and specifically to the Métis people who had to take up the challenge of redefining themselves. The author also encourages the reader to reflect on today’s nomadic, multiethnic, postmodern societies. Key words: Italian postcolonialism, identity dilemmas, Italian literature of migration, Erminia Dell’Oro.